The Repeatedly Elevated Fatty Liver Index Is Associated With Increased Mortality: A Population-Based Cohort Study - Lee, Chang-Hoon; Han, Kyung-Do; Kim, Da Hye; Kwak, Min-Sun (Frontiers in Endocrinology, 2021)
Aims: Nonalcoholic fatty liver disease(NAFLD) has a dynamic disease course, therefore repeated measurements of NAFLD status could have benefits rather than single one. The aim of this study was to investigate the effects of persistent NAFLD on the incidence of myocardial infarction(MI) and stroke and all-cause mortality by using repeated measurement of fatty liver index(FLI). Methods: About 3 million subjects who had undergone the health screening four times from 2009 until 2013. NAFLD was defined as an FLI≥60. FLI points were defined as the number of times participants meeting the criteria of NAFLD (0-4). Outcomes included all-cause mortality, MI and stroke. Results: The higher the FLI points, the higher the risk of all-cause mortality, MI and stroke (P for trend<0.001, all). Subjects with 4 FLI points had a higher risk of all-cause mortality(aHR,1.86; 95% CI,1.75-1.98;P<0.001), incidence of MI(aHR,1.3; 95% CI,1.21-1.40; P<0.001) and stroke(aHR,1.27;95% CI,1.19-1.37;P<0.001) after adjustment for age, sex, smoking, alcohol consumption, income, hypertension, dyslipidemia, diabetes, body mass index, and physical activity. When the 1st and the last FLI were compared, the ‘incident NAFLD’ group had a higher risk for death compared to the ‘no NAFLD’ group (aHR, 1.46; 95% CI,1.37-1.55), and the ‘regression of NAFLD’ group had a decreased risk for death compared to the ‘persistent NAFLD’ group(aHR,0.83; 95% CI,0.77-0.89). Conclusion: Repeated evaluations of NAFLD status based on FLI measurements could help physicians identify higher-risk groups in terms of mortality, MI and stroke. The association between FLI worsening or improvement and outcomes also suggests clinical benefits of the prevention and treatment of NAFLD.